Drug Drinking Motivation Reviewed From The Role Of Family On Pulmonary Tuberculosis Patients In Nganjuk Public Health Center - Cahya Eka Sudrajad; Sutrisno; Rahmania Ambarika (Universitas STRADA Indonesia, 2020)
Pulmonary Tuberculosis is a respiratory infectious disease caused by Mycobacterium tuberculosis and is contagious. Symptoms of pulmonary tuberculosis such as bleeding cough, cold sweat at night, shortness of breath and weight decreased. The role of the family in improving the motivation of taking medication such as preparing the medicine, accompanying control and reminding to drinking drug regularly This study aims to determine the relationship of the role of the family with the motivation to take medication in patients with pulmonary tuberculosis in Nganjuk Public Health Center.This type of research uses correlation approach. The number of samples were 38 respondents of pulmonary tuberculosis patients and also their families were obtained by purposive sampling method. Independent variable is family role and dependent variable is drug drinking motivation. The result of statistical test using Spearman Rho test got 0,000 significance value meaning p – value < 0,05, it can be concluded that H0 is rejected so that family role related to medication motivation in pulmonary tuberculosis patient at Nganjuk Public Health Center.The role of the family can increase the motivation to take medication so that it can reduce the risk of drug dropping and resistance to Anti Tuberculosis Drug (ATD) when undergoing treatment Process of pulmonary tuberculosis.